Interaction of HCF-1 with a Cellular Nuclear Export Factor - Mahajan, Shahana S. (J Biol Chem, 2002)
HCF-1 is a cellular protein required by VP16 to activate the herpes simplex virus (HSV) immediate-early genes. VP16 is a component of the viral tegument and, after release into the cell, binds to HCF-1 and translocates to the nucleus to form a complex with the POU domain protein Oct-1 and a VP16-responsive DNA sequence. This VP16-induced complex boosts transcription of the viral immediate-early genes and initiates lytic replication. In uninfected cells, HCF-1 functions as a coactivator for the cellular transcription factors LZIP and GABP and also plays an essential role in cell proliferation. VP16 and LZIP share a tetrapeptide HCF-binding motif recognized by the β-propeller domain of HCF-1. Here we describe a new cellular HCF-1 β-propeller domain binding protein, termed HPIP, which contains a functional HCF-binding motif and a leucine-rich nuclear export sequence. We show that HPIP shuttles between the nucleus and cytoplasm in a CRM1-dependent manner and that overexpression of HPIP leads to accumulation of HCF-1 in the cytoplasm. These data suggest that HPIP regulates HCF-1 activity by modulating its subcellular localization. Furthermore, HPIP-mediated export may provide the pool of cytoplasmic HCF-1 required for import of virion-derived VP16 into the nucleus.